The Relationship between Physical Activity and Body Mass Index (BMI) with Menstrual Cycle among Adolescent Girls in Balangtaroang Village, Bulukumba Regency - Bahrun, Suriani; Yusfira, Yuliana (Omni Health Journal, 2025)
Background: Menstrual cycle irregularities are common among adolescent girls and may lead to reproductive health problems if not addressed properly. Two major contributing factors are physical activity and body mass index (BMI), which influence hormonal balance and ovulatory function. Objective: This study aimed to determine the relationship between physical activity and BMI with menstrual cycle regularity among adolescent girls. Methods: An analytical observational study with a cross-sectional design was conducted involving 25 adolescent girls living in Balangtaroang Village, Bulukumba Regency. Physical activity data were obtained using a structured questionnaire, while BMI was calculated using height and weight measurements. Data were analyzed using the Somers’d test with a significance level of 0.05. Results: The results showed a significant relationship between physical activity and menstrual cycle (p = 0.044 < 0.05), while no significant relationship was found between BMI and menstrual cycle (p = 0.133 > 0.05). Conclusion: Physical activity is significantly associated with menstrual cycle regularity, while BMI is not. Balanced physical activity is recommended for adolescent girls to maintain reproductive health.